College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter 1 - Section 1.1 - Linear Equations - 1.1 Assess Your Understanding - Page 90: 52

Answer

No solution.

Work Step by Step

$\frac{2x}{x+3}=\frac{-6}{x+3}-2$ The LCD is (x-3) where $x\ne-3$ $(x+3)\frac{2x}{x+3}=(\frac{-6}{x+3}-2)(x+3)$ Multiply both sides by x+3. $(x+3)\frac{2x}{x+3}=(x+3)\frac{-6}{x+3}-2(x+3)$ Distribute, divide out common factors. $2x=-6-2(x+3)$ $2x=-6-2x-6$ Distribute, combine like terms. $2x+2x=-12-2x+2x$ Add 2x to both sides $4x=-12$ $\frac{4}{4}x=\frac{12}{4}$ Divide both sides by 4. $x=-3$ The equation has no solution because $x=-3$ creates a divide by zero error.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.